A continuous energy-based numerical approach to predict fracture mechanisms in masonry structures: CDF method. (December 2021) - Iannuzzo, A.; Block, P.; Angelillo, M.; Gesualdo, A.
Highlights: Energy-based investigation of settlements induced cracks in masonry structures. Continuous Displacement for Fracture (CDF) method is introduced and investigated. CDF is benchmarked against analytical and numerical solutions. CDF method leads to smeared cracks concentrated on narrow bands. CDF is mesh independent and captures slanted cracks crossing the elements. Abstract: In the present paper, we propose the Continuous Displacement for Fracture (CDF) method, a continuous energy-based numerical approach to find mechanisms and crack patterns exhibited by 2D masonry structures subjected to given loads and settlements. The structure is modelled through the normal, rigid, no-tension material, and the equilibrium problem is solved as the minimum of the total potential energy (TPE). With the CDF method the solution is sought in the space of continuous functions. The CDF performances are compared and illustrated against the PRD approach that finds the TPE minimum in the space of small, piecewise-rigid displacements. The CDF method is displacement-based approach, allowing for a direct control of the effects of foundation settlements. Some problems are proposed to benchmark the methodology against both PRD and analytical solutions to also clearly illustrate its peculiarities. Finally, its use and potentials are benchmarked and compared on a case study. CDF provides results in good agreement with both the PRD approach and another more sophisticated model. The main outcome is that, although more computationally cumbersome, CDF is mesh independent and perfectly captures a clear subdivision of the structural domain into macro-regions behaving as rigid or quasi-rigid bodies.